Low-dose hydrogen sulfide ameliorates cisplatin-induced hepatotoxicity in rats - Kudret Ensarioğlu Baktır; Onural Özhan; Hakan Parlakpınar; Ahmet Acet; Azibe Yıldız; Yusuf Türköz; Nigar Vardı; Recep Bentli; Mehmet Günata (Recent Trends in Pharmacology)
Objective: Cisplatin (CIS) is non-specific to the cell cycle, has a cytotoxic effect, and is used in many cancers. The side effects of CIS, such as hepatotoxicity, seriously limit its clinical use. This experimental study aims to prevent hepatotoxicity, one of the clinical side effects that cisplatin may cause. At the same time, Hydrogen sulfide (H2S) will be applied prophylactically and therapeutically and its effect levels will be compared. This study aims to contribute to the literature by preventing dose restriction due to the hepatotoxicity side effect of cisplatin, which plays an important role in cancer treatment, by prophylactic application of H2S. Our study investigated the protective and therapeutic efficacy of sodium hydrosulfide (NaHS, a donor of H2S), which activates the antioxidant system on CIS-induced hepatotoxicity. Method: Control (Vehicle), CIS (7.5 mg/kg CIS), H2S+CIS (10 µmol/kg NaHS+7.5 mg/kg CIS), CIS+H2S (7.5 mg/kg CIS+10 µmol/kg NaHS) groups were formed by using 35 rats in the study. At the end of the study, blood and liver tissue was taken, and histopathological and biochemical analyzes were performed. Results: It was determined that sinusoidal dilatation and congestion increased significantly in the CIS group and decreased in the H2S+CIS and CIS+H2S groups. Likewise, glycogen loss occurred in the CIS group, and a significant improvement was observed in the H2S+CIS group. In addition, significant deterioration was detected in malondialdehyde, catalase, glutathione, aspartate aminotransferase, alanine aminotransferase, and lactate dehydrogenase values in the CIS group compared to the control group. In contrast, significant improvements were observed in both the H2S+CIS and CIS+H2S groups compared to the CIS group. Conclusion: Both protective and therapeutic beneficial effects of H2S in CIS-induced hepatotoxicity were demonstrated by histopathological and biochemical analyses.